Factors İmpacting Entrepreneurial İntend of University Students: Role of Family Environment, Technology, Education, and Gender - Shrushti Hathi (International Journal of Advanced Science and Technology, 2020)
The government is putting in efforts that encourage the university students to select entrepreneurship. Yet there are students who do not have any intention to run their own start-ups. The main aim of the research is to study the effect of family environment, technology, education & gender on the entrepreneurship mindset of college students in India. This study is carried out by collecting data from 80 university students with the help of a questionnaire. This study has used multiple linear regression analysis on the data. The result of the study has shown that family environment, technology, education & gender substantially impact the entrepreneurship mindset of university students in India. This study also shows the collective as well as individual impact of family environment, technology, education & gender on the entrepreneurship mindset of the college students.